1997
DOI: 10.1128/jvi.71.10.7353-7360.1997
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional structural analysis of recombinant rotavirus-like particles with intact and amino-terminal-deleted VP2: implications for the architecture of the VP2 capsid layer

Abstract: Rotaviruses are the leading cause of severe infantile gastroenteritis worldwide. These viruses are large, complex icosahedral particles consisting of three concentric capsid layers enclosing a genome of eleven segments of double-stranded RNA (dsRNA). The amino terminus of the innermost capsid protein VP2 possesses a nonspecific single-stranded RNA and dsRNA binding activity, and the amino terminus is also essential for the incorporation of the polymerase enzyme VP1 and guanylyltransferase VP3 into the core of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(45 citation statements)
references
References 28 publications
3
40
0
2
Order By: Relevance
“…T = 1 symmetry of VP2 is needed for the initiation of the process of dsRNA synthesis [63]. Although the function of the N-terminal region (residues 1-132) is not understood well, this region seems to be important for the activation/ localization of the RNA-dependent RNA polymerase (VP1) and guanylyl transferase-methylase (VP3) into the virion center [64]. Our intrinsic disorder predisposition analysis revealed that the mean PPID of VP2 is 14.2% {Table 1}, indicating that it can be classified as moderately disordered protein.…”
Section: Structural Protein Vp2mentioning
confidence: 99%
See 1 more Smart Citation
“…T = 1 symmetry of VP2 is needed for the initiation of the process of dsRNA synthesis [63]. Although the function of the N-terminal region (residues 1-132) is not understood well, this region seems to be important for the activation/ localization of the RNA-dependent RNA polymerase (VP1) and guanylyl transferase-methylase (VP3) into the virion center [64]. Our intrinsic disorder predisposition analysis revealed that the mean PPID of VP2 is 14.2% {Table 1}, indicating that it can be classified as moderately disordered protein.…”
Section: Structural Protein Vp2mentioning
confidence: 99%
“…RNA binding activity and incorporation of VP1 and VP3 into viruslike particles (VLPs) [64]. The principal domain of VP2 (residues~100-880) associated with the RdRp polymerase activity also exhibits several IDPRs (residues 100-120, 140-144, and 192-200) {Fig.…”
Section: Structural Protein Vp2mentioning
confidence: 99%
“…4.1 (see also color insert) (Prasad et al, 1988;Yeager et al, 1990;Prasad et al, 1996). The innermost capsid layer is formed by 120 molecules of a 102 kDa protein VP2 arranged as 60 dimers on a T=I icosahedral lattice (Lawton et al, 1997b). Such an organization with two molecules in the icosahedral asymmetric unit has also been referred to as a 'T=2' structure (Grimes et al, 1998).…”
Section: Rotavirusmentioning
confidence: 99%
“…In rotavirus, the inner capsid protein VP2 is proposed to have a dual role in defining the overall architecture of the virion, not only defining the icosahedral architecture of the capsid layers, but also acting as a scaffold for the proper assembly of the protein and nucleic acid compo-nents within the viral core (Prasad et alo, 1996;Lawton et al, 1997b). The inner capsid layer is formed from 60 dimers of quasiequivalent VP2 molecules organized on a T=I icosahedral lattice ( Fig.…”
Section: Scaffoldingmentioning
confidence: 99%
See 1 more Smart Citation